Medical and scientific publishing author, editor, and reviewer perspectives - Markovac, Jasna; Kleinman, Molly; Englesbe, Michael J. (Academic Press, an imprint of Elsevier, 2018)
Very few doctors and scientists receive any sort of systematic training in publishing, editing, and reviewing scholarly articles, despite the central importance of that work for scientific research and for their careers. Medical and Scientific Publishing will help fill the gap and help readers to: Understand processes of scientific and medical publishing Understand the role of an academic in medical publishing Become a better scientific communicator Develop skills to effectively serve as the editor of a medical journal Medical and Scientific Publishing is based on a successful course at the University of Michigan Medical School for third and fourth year medical students. The course teaches students not just how to write scientific and medical articles, but addresses key issues surrounding copyright, ethics, open access and much more. Students will build a strong foundation on how to do peer review and how to be authors and editors which are important skills in building a professional career. Covers a full range of essential information - explanation of publishing licenses, copyright and permissions, how to do peer review, how to write effectively, how journal publishing works, and much more Emphasizes rigor, quality, and scientific integrity in writing, editing, and publishing Focuses on authorship and editorial skills by experienced authors and publishers.